MISTISISME ISLAM (Sebuah Dilema dan Tinjauan Masa Depan) - Abdul Hakim (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2019)
AbstractThe assumption who says that Sufism as a cause of poverty, backwardness, and stagnation is a misnomer because scientific research has been done by r. Pieris mentioned that India's Sikhs seized economic position because it combines the simplicity and the hard work of teaching, research and student groups mention that Geetz relatively richer than at abangan caused due to the attitude of a group of students is simple and avoids the lavish ceremony but workers hard. Likewise, some Sufi figures who have many scientific works such as Al-Farabi and Al-Ghazali.However, Sufism's future will be more commonly used with model neo-Sufism, in terms of a model that requires the batiniyah religious active life and engage in cooperation. Once in a while get rid of yourself to uzlah it might be worthwhile if it is done to energize your insights and views that was the starting point for the involvement and activity in the community. Such a model is like that offered by Hamka (Modern Tasauf) and Fazlurrahman (Neo-Sufism). Sufism this model trying to maintain the positive outcomes of modernization or development of science by filling the void that exists in him.Keywords: mistisme, the dilemma, Preview the future